Ekoteologi: Menjawab Krisis Lingkungan dalam Terang Iman Kristen : Materi Pengabdian Kepada Masyarakat Dosen dan Mahasiswa Prodi S-2 PAK IAKN Tarutung Tahun 2025 di Desa Situmeang Pintu Bosi Kecamatan Sipoholon, Tapanuli Utara - Liberto Ripan Petrus Hutagalung; Hisardo Sitorus; Baginda Sitompul (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
The environmental crisis is a global issue that has become increasingly evident and directly affects human life, including rural communities. Deforestation, environmental pollution, and changes in human lifestyles reflect an imbalanced relationship between humanity and nature. From a Christian faith perspective, the environmental crisis is not merely an ecological or social problem. This article aims to examine ecotheology as a foundation of Christian faith in responding to environmental crises, while also describing its practical implementation through a Community Service program conducted by lecturers and students of the Master’s Program in Christian Religious Education at IAKN Tarutung in 2025 in Situmeang Pintu Bosi Village, Sipoholon District, North Tapanuli Regency. The method employed is a qualitative approach using a participatory service model, which includes ecotheological material presentations, Bible-based reflective discussions, and the accompaniment of simple environmental care actions with the local community. The service materials emphasize the understanding of God as the Creator and Owner of all creation, the cultural mandate and stewardship, the reality of sin and its impact on the degradation of creation, and the role of the church and believers in preserving environmental integrity. The results indicate an increased theological understanding among the community regarding Christian responsibility toward the environment, along with the growth of ethical awareness to care for nature through concrete actions in daily life. This activity affirms that ecotheology is not merely conceptual, but has practical relevance in fostering faith-based ecological awareness.